N.N. BERKOVA'S TEXT BOOK “KAZAKHSTANI NON-FICTION FILM ON THE INTERACTION OF NATURE AND SOCIETY” IS PUBLISHED - А. Baigozhina (Central Asian Journal of Art Studies, 2017)
The author of the review for the textbook “Kazakhstani non-fiction film on the interaction of nature and society” by the film critic N.N. Berkova talks about the depth of the issues of “non-fiction film on the interaction of nature and society,” about the attempt to systematically describe the republican films on this topical theme. The author of the review draws attention to evolution and the dynamics of the process as a whole in the broad context of world cinema highlighted by Berkova, points to the reasoning of periodization with the characteristic of each period and the indication of all significant works, the identification of the specifics and features of different genres, including the popular science film genre. One of the conclusions of the textbook for teaching students is significant - environmental film in the broadest sense, is a film that shapes the worldview of the audience.